Sarcopenia and decline in appendicular skeletal muscle mass are associated with hypoperfusion in key hubs of central autonomic network on 3DSRT in older adults with progression of normal cognition to Alzheimer's disease. Issue 1 (16th December 2022) - Demura, Taichi; Okuno, Tazuo; Miwa, Takaki; Iritani, Osamu; Nakano, Hiroyuki; Yamamoto, Junpei; Shiga, Hideaki; Kodera, Kumie; Morimoto, Chihiro; Demura, Noboru; Morimoto, Shigeto
Abstract : Aim: Although sarcopenia is common in patients with Alzheimer's disease (AD), the neural substrates involved remain unclear. We investigated the relationship between sarcopenia, as well as its definition components, and regional cerebral blood flow (rCBF) in older adults with progression of normal cognition to AD. Methods: 99m Tc‐ethyl‐cysteinate‐dimer single‐photon emission computed tomography was carried out in 95 older adults with progression of normal cognition to AD (40 men and 55 women, mean ± SD age 80.9 ± 6.8 years). The associations of rCBF determined by 3‐D stereotactic region of interest template software, with sarcopenia and its definition components, slower gait speed, weaker grip strength, and decline in appendicular skeletal muscle mass index (ASMI) were analyzed. Results: Logistic regression analysis adjusted by age, sex, mini‐mental state examination score and education showed that sarcopenia as well as ASMI less than the cut‐off (men 7.0 kg/m 2, women 5.7 kg/m 2 ) were associated with significantly reduced rCBF in the key hub of the central autonomic network, including the insula, anterior cingulate cortex, subcallosal area, rectal gyrus, hypothalamus, amygdala and caudate head. Sarcopenia and ASMI decline were associated with hypoperfusion in the aforementioned cortical hubs of the central autonomic network in men, but with hypoperfusion of the hypothalamus in women. Linear regression analysis showed significant correlations of ASMI/cut‐off with rCBF in the bilateral medial frontal cortex, as well as rCBF in the aforementioned key hubs. Conclusions: Hypoperfusion in key hubs of central autonomic network is implicated in the emergence of sarcopenia, probably through ASMI decline in vulnerable older adults. Geriatr Gerontol Int 2023; 23: 16–24 . Abstract : SPM8 results from group comparison of regional cerebral blood flow (rCBF). Subjects with sarcopenia ( n  = 56) showed significant reduction of rCBF in the bilateral anterior cingulate cortex and left insula compared to those without sarcopenia ( n  = 39).